2022
DOI: 10.1063/5.0119355
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies on heavy fluid layers with reshock

Abstract: The Richtmyer-Meshkov instability of a heavy fluid layer with reshock is investigated experimentally and theoretically, to reveal the mechanisms of the interfacial instabilities and motions of waves and interfaces under reshock conditions. Three kinds of heavy fluid layers with different thicknesses in unperturbed and perturbed cases are considered, highlighting the effects of initial layer thickness on the interface evolution. A general one-dimensional theory for describing the interaction between unperturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…After the shock impact, phase reversal generally arises at the second interface of the heavy fluid layer (Meyer & Blewett 1972). Previous fluid-layer studies have indicated that, once phase reversal of the second interface is accomplished, the spike continually grows downstream so that freeze-out cannot be achieved by the interface coupling (Liang et al 2020;Cong et al 2022). Consequently, the freeze-out for the second interface needs to be achieved before phase reversal.…”
Section: Supplementary Condition For the Second Interface's Freeze-outmentioning
confidence: 99%
See 2 more Smart Citations
“…After the shock impact, phase reversal generally arises at the second interface of the heavy fluid layer (Meyer & Blewett 1972). Previous fluid-layer studies have indicated that, once phase reversal of the second interface is accomplished, the spike continually grows downstream so that freeze-out cannot be achieved by the interface coupling (Liang et al 2020;Cong et al 2022). Consequently, the freeze-out for the second interface needs to be achieved before phase reversal.…”
Section: Supplementary Condition For the Second Interface's Freeze-outmentioning
confidence: 99%
“…This leads to the model's inability to correctly characterize the parameters required for freeze-out. Second, reverberating waves within the layer continually interact with fluid-layer interfaces, resulting in additional Rayleigh-Taylor effects and stretching effects (Liang et al 2020;Cong et al 2022), thereby causing the freeze-out theory of Mikaelian (1995) to be invalid. In other words, the presence of reverberating waves makes it difficult to achieve freeze-out for fluid-layer interfaces by interface coupling alone since, even if the interface coupling leads to freeze-out of perturbation growth, the reverberating waves would destroy the freeze-out state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial instability driven by successive shocks/rarefactions or rarefactions/shocks is more complex than that caused by a single wave. Previous studies, involving reshock-interface interactions (Hill, Pantano & Pullin 2006;Lombardini et al 2011;Li et al 2019Li et al , 2021 and fluid-layer behaviours (Liang & Luo 2021;Cong et al 2022), have primarily focused on the interfacial instabilities induced by different waves. In these studies, the constraints imposed by rigid walls or fluid-layer interfaces cause shocks and rarefactions to bounce back and forth, resulting in repeated interactions with the interface.…”
Section: Introductionmentioning
confidence: 99%
“…2019, 2021) and fluid-layer behaviours (Liang & Luo 2021; Cong et al. 2022), have primarily focused on the interfacial instabilities induced by different waves. In these studies, the constraints imposed by rigid walls or fluid-layer interfaces cause shocks and rarefactions to bounce back and forth, resulting in repeated interactions with the interface.…”
Section: Introductionmentioning
confidence: 99%